Elimination du méthyle violet, en solution aqueuse par un matériau biodégradable en présence des irradiations ultrasonores - Mabrouka BOUSALEM; Fella BENTRIA (My University, 2022)
This work aims to study and model the adsorption of a basic dye, methyl violet (MV) by the grains of hazelnut shells (CN), in an aqueous medium in the absence and in the presence of ultrasonic irradiation. Low frequency. The physicochemical characterization of the grains of hazelnut shells shows that its suspension has a basic character capable of increasing the pH value of distilled water from 5.5 to 5.8. The zero load point of CNS is 6.1. The effects of operating parameters on the adsorption of MV by the chosen adsorbent in the absence and in the presence of ultrasound have been studied and discussed. The increase in the initial concentration of MV leads to an increase in adsorption. MV removal increases with increasing biomaterial dose. The removal is significantly improved in the presence of ultrasound due to the improvement of mass transfer phenomena. On the other hand, the quantity adsorbed per unit mass of CN seeds decreases when the dose of adsorbent increases. The adsorption of MV is disadvantaged by high temperatures because the overall dye adsorption process is exothermic. The ionic strength disadvantages the adsorption of MV. Basic PHS were found to be the most favorable for MV adsorption. A significant improvement in the adsorption capacity of MV by the chosen adsorbent in the presence of ultrasound in distilled water compared to that observed in natural waters (mineral and sea). The study and the modeling of the kinetics of adsorption of MV by the grains of the hazelnut shells make it possible to release several results on the mechanisms likely to govern the kinetics of adsorption. Pseudo-first-order and pseudo-second-order models are u sed to analyze kinetic data. The results obtained show that the adsorption kinetics are adequately described by the pseudo-second order equation. The two limiting steps of adsorption kinetics are transfer through the outer film and intraparticle diffusion. This study showed that the combination adsorption-ultrasound is a very promising method and can be an alternative technique to conventional methods. ------------------------------------------------------------------------------------- بواسطة حبيبات قشور البندق )VM( يهدف هذا العمل إلى دراسة ونمذجة امتصاص صبغة أساسية، ميثيل البنفسج في وسط مائي في حالة وجود أو غياب الإشعاع فوق صوتي منخفض التردد. ،)NC( يوضح التوصيف الفيزيائي والكيميائي لحبوب قشور البندق أن تعليقها له خاصية أساسية قادرة على زيادة قيمة الأس . الهيدروجيني للماء المقطر من 5.5 إلى 5.5 . ونقطة التحميل الصفرية للنفثالينات المكلورة هي 1.6 بواسطة الممتزات المختارة في غياب الموجات فوق VM تمت دراسة ومناقشة تأثير معاملات التشغيل على امتزاز مع زيادة جرعة المواد VM إلى زيادة الامتزاز. تزداد إزالة VM الصوتية وفي وجودها، وتؤدي الزيادة في التركيز الأولي لل الحيوية. تم تحسين الإزالة بشكل ملحوظ في وجود الموجات فوق الصوتية بسبب تحسن ظاهرة انتقال الكتلة.من ناحية أخرى، بدرجات الحرارة VM تقل الكمية الممتصة لكل وحدة كتلة من بذور النفثالينات عندما تزداد جرعة الممتزات. يتأثر امتصاص المرتفعة لأن عملية امتزاز الصبغة الكلية طاردة للحرارة، والقوة الأيونية تضر بامتزاز MV . أثبت الأس الهيدروجيني الأساسي بواسطة الممتزات المختارة في وجود الموجات فوق VM أنه الأكثر ملاءمة لامتزاز الصبغة. تحسن كبير في قدرة امتصاص الصوتية في الماء المقطر مقارنة بتلك الملحوظة في المياه الطبيعية )المعدنية والبحرية(. بواسطة حبيبات قشور البندق تجعل من الممكن إطلاق العديد من النتائج على VM دراسة ونمذجة حركية امتزاز الآليات التي يحتمل أن تتحكم في حركية الامتزاز. تُستخدم النماذج من الدرجة الأولى والنماذج من الدرجة الثانية لتحليل البيانات الحركية. تظهر النتائج التي تم الحصول عليها أن حركية الامتزاز موصوفة بشكل مناسب بواسطة معادلة الدرجة الثانية. يتم نقل الخطوتين المحددتين لحركية الامتزاز من خلال السطح الخارجي والانتشار داخل الجسيمات. أظهرت هذه الدراسة أن الجمع بين الامتزاز بالموجات فوق الصوتية طريقة واعدة للغاية ويمكن أن تكون تقنية بديلة للطرق التقليدية --------------------------------------------------------------------------------------------- La caractérisation physicochimique des grains des coquilles de noisette montre que sa suspension à un caractère basique capable d’augmenter la valeur du pH de l’eau distillée de 5,5 à 5,8. Le point de charge zéro des CN est de 6,1. Les effets des paramètres opératoires sur l’adsorption du MV par l’adsorpant choisi en l’absence et en présence des ultrasons ont été étudiés et discutés.L’augmentation de la concentration initiale du MV entraîne un accroissement d’adsorption. L’enlèvement du MV augmente avec l'augmentation de la dose du biomatériau. L’enlèvement est significativement amélioré en présence d'ultrasons du fait de l'amélioration des phénomènes de transfert de matière.Par contre, la quantité adsorbée par unité de masse des graines des CN diminue quand la dose d’adsorbant augmente. L’adsorption du MV est défavorisée par les hautes températures car le processus global d’adsorption des colorants est exothermique.La force ionique défavorise l’adsorption du MV. Les pH basiques se sont avéré les plus favorables à l’adsorption du MV. Une amélioration significative de la capacité d’adsorption de MV par l’adsorpant choisi en présence des ultrasons dans l’eau distillée par rapport à celle observée dans les eaux naturelles (minérale et de mer). L’étude et la modélisation des cinétiques d’adsorption du MV par les grains des coquilles de noisette permettent de dégager plusieurs résultats sur les mécanismes susceptibles de régir les cinétiques d’adsorption. Les modèles de pseudo-premier ordre et pseudo-second ordre sont utilisés pour analyser les données cinétiques. Les résultats obtenus montrent que les cinétiques d’adsorption sont adéquatement décrites par l’équation de pseudo-second ordre. Les deux étapes limitantes des cinétiques d’adsorption sont le transfert à travers le film externe et la diffusion intraparticulaire. Cette étude a montré que la combinaison adsorption-ultrasons est une méthode très prometteuse et peut être une technique alternative aux méthodes classiques.